Assessment of High Speed Spindle Accuracies - A P, Arun; A, Faizur Rahman; V., Manivelmuralidaran; K., Krishnamoorthi (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The spindle error contributes to 25 percent of the error sources of the work piece in- accuracies. The 70 percent of the spindle errors are due to thermal errors that occurs in the spindle. The heat generation in high-speed built-in motorized spindle is of important concern in high speed machining. It is necessary to predict the heat generation in spindle body virtually so as to judge machine capability. The thermal prediction will also help in taking precautions to avoid inaccurate parts being produced as well to avoid the chances of bearing seizure leading to catastrophic failure of spindle. In this paper the thermal behavior of high-speed motorized spindle is investigated through three dimensional analysis and experimentation validation is given for the same.